NEUROPROTECTIVE EFFECT OF HYDROALCOHOLIC EXTRACT OF AMARANTHUS TRICOLOR LEAVES ON EXPERIMENTAL ANIMALS - BALA, VIDHAN CHAND; ABID, MOHD (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The research work deals with the screening of hydroalcoholic extract of Amaranthus tricolor (HAEATL) leaves for central nervous system activity (anti-stress, nootropic, and anti-cataleptic activity). Methods: The screening of scopolamine and different model-induced neurodisorder rats were treated with 200 and 400 mg/kg body weight dose of hydroalcoholic extract of A. tricolor lives in 7 days’ experimental schedule. It has been reported that the antioxidant, hepatoprotective, hematological, and antimicrobial activities. Results: The result of the study reflected that HAEATL (200 and 400 mg/kg) was effective in all methods and showed anti-stress, nootropic, and anti-cataleptic activity in a dose-dependent manner. The results are represented that the HAEATL produce the significant decreased the swimming time, increased the anoxia time, decreased level of biochemical parameters such as glucose and cholesterol except blood urea nitrogen, decreased level of white blood cell and red blood cell, and more significantly decreased the catalepsies score on 7th day compared to the control group. Conclusion: The above valuable animal study, we concluded that the HAEATL showing significantly affect compeer to the disease control group on neuroprotective activity.